Association between aspirin use and cardiovascular outcomes in ALLHAT participants with and without chronic kidney disease: A post hoc analysis. Issue 2 (19th December 2020) - Desai, Niraj; Wilson, Brigid; Bond, Michael; Conant, Alexander; Rahman, Mahboob
Abstract: It is unclear whether aspirin is beneficial for prevention of CVD in patients with CKD. We performed a secondary analysis of the ALLHAT trial to assess the effect of baseline aspirin use on nonfatal myocardial infarction (MI) or fatal coronary heart disease (CHD), all‐cause mortality, and stroke. Baseline characteristics of aspirin users and nonusers were used to generate propensity‐matched cohorts. Using conditional Cox proportional hazard regression models, we examined the effect of aspirin on the outcomes in the cohort at large and across 3 levels of kidney function (eGFR ≥90, 60–89, and <60). 11 250 ALLHAT participants reported using aspirin at baseline. The propensity‐matched dataset included 6894 nonusers matched with replacement to achieve a balanced analysis population ( n = 22 500). Risk of fatal CHD or nonfatal MI (HR = 0.94, 95% CI 0.86–1.02) and stroke (HR = 1.01, 95% CI 0.89–1.15) was not significantly different between groups. Aspirin users were at significantly lower risk of all‐cause mortality compared to nonusers (HR = 0.82, 95% CI 0.76–0.88). Aspirin use was not associated with incidence of fatal CAD or nonfatal MI in patients with CVD (HR = 0.93, CI 0.84–1.04) or without CVD at baseline (HR = 1.04, CI 0.82–1.32). Results were consistent across strata of GFR (interaction p value NS). In hypertensive patients at high cardiovascular risk, aspirin use is not associated with risk of nonfatal MI, fatal CHD, or stroke; however, aspirin use is associated with lower risk of all‐cause mortality. These results are consistent across baseline eGFR.